Rural perception on tourists' willingness to revisit in rural tourism: A study of Ma Wei Yi Folk culture village, Shaanxi Province, China - Xu, Ting (Universidade Federal de Santa Maria, 2023)
The development of rural tourism destinations in China is confronting multiple issues, including blind expansion and a repetitive developmental model, causing the sector to enter a vicious competition cycle. The perception among tourists of rural tourism destinations, and their willingness to revisit places will provide insights for service providers that will enable them to form better strategies to stand out in the fiercely competitive market. Understanding tourist perception will enable providers to contribute to the construction of rural tourist destinations. Taking Ma Wei Yi Folk Culture Village as a case study, this paper combines the development status of rural tourism in Ma Wei Yi, obtains first-hand data through questionnaire interviews, verifies the research hypothesis, and uses Pearson coefficient to carry out correlation analysis. The paper concluded that tourists’ rural perception has a positive and strong impact on their willingness to revisit, and its factors have different impacts. According to the empirical results, tourist destination providers should pay attention to rural perceptual development in their follow-up development and operation processes. They can effectively attract tourists to visit multiple times, enhance tourist’s sense of enjoyable experience, and achieve sustainable development.